Unaltered TNF-α production by macrophages and monocytes in diet-induced obesity in the rat - Jones Jessica E; Bozinovski Steve; Velkoska Elena; Bedoui Sammy; Anderson Gary P; Morris Margaret J (BMC, 2005)
Abstract Background Recent findings have established an association between obesity and immune dysfunction. However, most of the studies investigating the effects of obesity on immune function have been carried out in genetically obese rodent models. Since human obesity is mostly due to intake of a high fat diet and decreased energy expenditure, we asked whether immunological defects also occur in diet-induced obesity. Specifically, we focused on the function of monocytes and macrophages, as these cells are thought to be involved in the low-grade inflammation present in obesity. Methods Male Sprague-Dawley rats were fed a high-fat or a standard chow diet for either 2 or 10 weeks. At the end of the intervention period animals were anaesthetised, blood collected for determination of plasma mediator concentrations and lipopolysaccharide (LPS) stimulated production of TNF-α by monocytes. LPS stimulated production of TNF-α in alveolar macrophages was also determined. Results High-fat feeding for either 2 or 10 weeks resulted in significant increases in fat mass and serum leptin. Although increased serum leptin has previously been linked to modulation of innate immunity, we found no significant difference in the LPS stimulated production of TNF-α by either blood monocytes or alveolar macrophages between the dietary groups. Furthermore, we failed to find a significant increase in circulating TNF-α concentrations in obese animals, as reported for genetically obese animals. Conclusion Our data suggest that defects in innate immune function observed in genetically obese animals are not mimicked by dietary obesity, and may more likely reflect the gross abnormality in leptin function of these models. Further work is required delineate the effects of dietary obesity on inflammatory state and immune function.